Paralysing international criminal justice - Malekian, Farhad (New York : Nova SciencePublishers, Inc., 2020)
"Even though the injustices occurring against the Palestinians are alarming, no government is assisting the victims. The gavel of lady justice has been stolen by the permanent members of the Security Council, and thus, no state has spoken out against the injustices. The judges and prosecutors of the international courts are threatened by the dialogues of the powerful authorities, and they even celebrate the mourning of the broken dreams of the innocent children. The Palestinian population has been subjected to genocide, annihilation, banishment, and terror at the hands of the grandchildren of those who themselves greatly suffered from the genocide in Europe - and still this situation has been referred to as the deal of the century. For a long period of time, the territorial integrity, the traditional sovereignty, the spiritual capital, and the international legal personality of one of the oldest nations of the world have been suffering, arguably to feed the political laundering of other nations. Without any hesitation, the principles of dignity, justice, and equality allegedly upheld by the United Nations should be questioned given the inequity in voting and membership within the organisation. This book seeks bare justice and to tackle the grave violations of international criminal justice in Palestine and elucidate the fact that the notions of irresponsibility, non-accountability, and impunity are stronger than the corpus of the permanent International Criminal Court"--
Struggling for companionate justice -- Crimes of justice -- The notion of international legal personality -- Traditional recognition of Palestine -- Violations of international peremptory criminal law -- The mens rea of political laundering crucifying Al-Quds/Jerusalem -- Actus reus of the declaration implying the guilty mind -- Characterising dignity through the exploitation of legal personality -- Conclusion.
Includes bibliographical references (pages 305-336) and index.
Keywords: Criminal justice, Administration of; Victims of crimes (International law); International criminal courts; International Criminal Court; Palestinian Arabs -- Crimes against -- Israel; Discrimination in criminal justice administration -- Israel; Palestinian Arabs -- Civil rights -- Israel; United Nations. -- Security Council; Victimes d'actes criminels (Droit international); 0; Palestiniens -- Crimes contre -- 0; 0; Palestiniens -- Droits -- 0; International Criminal Court; United Nations. -- Security Council; Criminal justice, Administration of; Discrimination in criminal justice administration; International criminal courts; Palestinian Arabs -- Civil rights; Palestinian Arabs -- Crimes against; Victims of crimes (International law); Israel